CONVERGENCE OF CYNTACTIC AND STYLISTIC FIGYRES (Scientific journal of the Fergana State University, 2024)
The article examines the convergence of syntactic-stylistic means with syntactic-stylistic figures, stylistic changes in the structure of speech, and the influence of speech on the artistic and aesthetic function. it can be used together with other syntactic and stylistic means in speech to identify the phenomenon of stylistic convergence. The study of syntactic-stylistic figures from the point of view of convergence shows that the interaction of various syntactic-stylistic figures can be the basis for determining their place not only as a functional unit, but also as a stylistic figure, for studying the artistic and aesthetic formation of speech at a high level.